Worktext in database management system : complete with hands-on exercises - San Luis, Rosemarie R. (Intramuros, Manila, Philippines : Mindshapers Co. Inc., 2013)
This work text was written out of a felt need for a simplified instructional guide in Database Management System (DB<A).
Chapter 1 A brief history of database systems -- Chapter 2 Database management system -- Chapter 3 Getting started with MS access 2010 -- Chapter 4 Working with MS access table -- Chapter 5 Modifying the tables -- Chapter 6 Working with forms -- Chapter 7 Sorting, filtering and creating a relationship with table -- Chapter 8 Setting queries.
Keywords: DATABASE MANAGEMENT